Spray Deposition and Control of Botrytis cinerea on Grape Leaves and Bunches: Part 1 (Table Grapes) - Brink, J.C.; Calitz, F.J.; Fourie, P.H. (South African Journal of Enology and Viticulture, 2016)
Insufficient quantity but also quality of spray deposition on susceptible grapevine tissue (i.e. target sites) and favourable conditions for pathogens could lead to control failure during high disease pressure situations. To determine deposition quantity and quality benchmarks for biologically effective spray deposits, bunches and leaves of table grapes (Waltham Cross) were sprayed at various growth stages, using different application volumes of a mixture of fenhexamid and a fluorescent tracer pigment and subsequently dusted with dry conidia of Botrytis cinerea where after infection levels on pedicels, receptacles and leaves were determined. Pigment deposition quantity and quality were determined from photos of sprayed parts taken with a digital camera under a stereo microscope and black light illumination at ×30 or ×10 magnifications and assessed with digital image and Hoerl regression analyses. The deposition quantity resulting in 75% control of B. cinerea infection (FPC75 values) was calculated from biological efficacy curves (sigmoidal regression analyses) for leaves and for each growth stage, for pedicels and receptacles. Deposition quantity and quality measurements correlated favourably with Botrytis infection. An optimal deposition value for the control of B. cinerea was determined by increasing spray volume, however by increasing spray volume and deposition quantity or quality levels past this optimum will not significantly improve disease control further. It was indicated that efficacy of agricultural chemicals could be influenced by improving both deposition quantity and quality, quantifiable by digital image analyses of fluorescent pigment deposition. FPC75 values obtained in this study can be used as benchmarks to evaluate future spray application in vineyards.